The Influence of the Principal Leadership Model and Teacher Motivation: A Study on the Performance Analysis of Senior High School Teachers in Ngawi District - Muhammad Shoffa Saifillah AlFaruq; Roficha Yuliani (JETL (Journal of Education, Teaching and Learning), 2025)
Leadership and motivation models are components that must be possessed by school principals and teachers in the scope of education. The existence of a superior leadership and motivation system can increase the value of the institution. This study aims to determine the influence of the principal's leadership model and teacher motivation partially and silmulantly on teacher performance. This research method is descriptive quantitative with a determination technique using total sampling, so that the number of population and samples in this study amounted to 80 subjects. The data collection technique uses a questionnaire that has been validated by the validator with a validity value of 0.86 and a reliability of 0.76 and research documentation. The data analysis technique used in this research uses the t test and the f test. The results of the persial test research are 1) It is known that the value of sig. The influence of the principal's leadership model on teacher performance is 0.000 < 0.05 and the value of tcount 5.764>ttable 1.665. 2) The value of sig. for teachers' motivation for teacher performance is as much as 0.0027 ttable 1.665. 3) The value of sig. For the leadership model of the principal and the motivation of teachers simultaneously on teacher performance, which is 0.000< 0.05 and the value of tcount 24.508 > ttable 3.12. The results of this study can be concluded that there is an influence of the principal's leadership model and teachers' motivation both physically and simultaneously on the performance of Senior High Schools in Ngawi District.